THE EFFECT OF NEOLOGISMS ON TRANSLATION - Shokirov Manuchekhr Shamsidinovich, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  study  investigates  the  techniques  utilized  by  simultaneous interpreters to manage neologisms during interpretation. It examines the difficulties interpreters  encounter  and  proposes  methods  to  enhance  interpretation  quality. Simultaneous interpretation demands real-time processing and translation of speech, posing distinct challenges. Speech compression has emerged as a technique to enhance accuracy  and  understanding.  This  paper  explores  the  implementation  of  speech compression in simultaneous interpretation and its effects on interpreter performance.